Dietary Bile Salt Types Influence the Composition of Biliary Bile Acids and Gut Microbiota in Grass Carp - Xiong, Fan; Wu, Shan-Gong; Zhang, Jing; Jakovlić, Ivan; Li, Wen-Xiang; Zou, Hong; Li, Ming; Wang, Gui-Tang (Frontiers in Microbiology, 2018)
Lipid metabolism can influence host’s health. There is increasing evidence for interplay between two key regulating factors in lipid metabolism: bile acids (BAs) and gut microbiota. However, very little is known about how types of different diet-supplemented bile salts (BS) influence this interaction in vivo. We sought to explore these relationships using grass carp (Ctenopharyngodon idellus), which often suffers functional disorder of liver and gallbladder. We studied fluctuations of BAs in the gall and changes of microbial communities in the gut in response to seven different diets: five different BS, chelating BS agent and control. The BS comprised two primary BS (sodium taurochololate (TCAS) and sodium taurochenodeoxycholate (TCDCAS)), sodium tauroursodeoxycholate (TUDCAS), and two secondary BS (sodium taurodeoxycholate (TDCAS) and sodium taurolithocholate (TLCAS)). Supplementation of primary BS caused a more significant fluctuation of biliary BAs than secondary BS, and TCAS caused a more prominent increase than TCDCAS and TUDCAS. For the gut microbiota, primary BS tended to increase their diversity and induce community succession, secondary BS resulted in a higher Firmicutes/Bacteroidetes ratio, while TUDCAS had no significant effects. Changes of the gut microbiota triggered by different types of BS caused alteration in BAs biotransformation. Two obesity associated families, Lachnospiraceae and Ruminococcaceae were positively correlated with biliary cholic acid (CA), taurochenodeoxycholic acid (TCDCA) and deoxycholic acid (DCA). As both primary and secondary BS resulted in increased synthesis of toxic secondary BAs by the gut microbiota, future medical studies should pay closer attention to gut microbiota when considering BA treatment.